Pengaruh Pengujian pH Terhadap Kesegaran Cabai Rawit: Studi Kasus Pada Produk Pangan Berbasis pH - Manika, Salwa Ayu; Awalyah, Reika; Hakim, Fathan Abdul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Food is one of the main needs of the human body. We as living beings need to consume food as the main source of energy for the body in order to carry out daily activities. But we also need to remember the freshness of the food we will consume. It should be noted whether the food is still suitable for consumption or not. This study was conducted by testing fresh cayenne pepper (A) and rotten cayenne pepper (B) with organoleptic observations and pH testing using pH paper. This study aims to determine information about differences in organoleptic quality and pH between fresh cayenne pepper and rotten cayenne pepper. This study shows that organoleptic observations and pH testing can be done to prove the freshness of food ingredients. However, if only pH testing is done, it cannot be too influential to determine the freshness of a food ingredient.